2015
DOI: 10.1136/bjsports-2015-094705
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of groin injury in senior football: a systematic review of prospective studies

Abstract: Background Groin injuries are troublesome in men's and women's football.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
106
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 45 publications
6
106
0
2
Order By: Relevance
“…This has made it difficult to synthesise the findings of clinical research in this area. A systematic review of groin injury epidemiological studies highlighted the need for prospective studies to be of higher quality, and report detailed data on specific diagnostic categories 3. A recent consensus meeting standardised the taxonomy and terminology used to describe hip and groin pain, and provided a guideline to be used by clinicians and researchers 15.…”
Section: Introductionmentioning
confidence: 99%
“…This has made it difficult to synthesise the findings of clinical research in this area. A systematic review of groin injury epidemiological studies highlighted the need for prospective studies to be of higher quality, and report detailed data on specific diagnostic categories 3. A recent consensus meeting standardised the taxonomy and terminology used to describe hip and groin pain, and provided a guideline to be used by clinicians and researchers 15.…”
Section: Introductionmentioning
confidence: 99%
“…Sports injuries are inherent to the sports practice, and are quite familiar to the majority of athletes, as shown by numerous epidemiological studies [1,2]. In professional or elite football, for example, each player suffers a mean of two sports injuries during a single competitive season [3,4], which causes a significant impact to the club.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, injuries also have a negative impact on the team's performance. Waldén et al [1] indicate that the higher are the injury rates in elite European soccer, the poorer the team performance is. In addition to the economic and sportive consequences for the clubs, injuries may produce other consequences for the player (need for special practices, loss of fitness, time spent as a substitute, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In soccer, groin injuries account for up to 19% of all injuries [30], while the estimated prevalence may be as high as 70% [26]. A recent systematic review, reported a high rate of hip and groin injuries in ice hockey and football code sports such as Australian football, Gaelic football, and rugby [17].…”
Section: Introductionmentioning
confidence: 99%